Genetic Control of Root Weight, Root Volume and Root to Shoot Weight Ratio in Peas - Saleh, Ghizan; Gritton, Earl T. (1988)
The genetic control of root weight, root volume and root to shoot weight ratio was studied in peas (Pisum sativum L.) at flowering. The four populations used were developed from crosses between lines and cultivars differing in size of the root systems. Plants of the F1, F2 , back cross and parental generations were evaluated in pots filled with soil: sand mixture, in a completely randomized design. A generation means analysis was used to determine the inheritance of the root characteristics. Root weight and volume exhibited moderate to high broad-sense heritability (0.41 - 0.81 for root weight, and 0.44 - 0.77 for root volume). Additive and dominance effects were important in the inheritance of root weight and volume in all populations, while epistatic effects were important only in two populations. The importance of the genetic parameters in the inheritance of root to shoot weight ratio was unclear. With the presence of large additive effects and high heritability, estimates for root weight and volume, selection for superior pure lines with large root systems should be effective.